Argentina: Soil Organic Carbon Sequestration Potential National Map. National Report. Version 1.0. Year: 2021 - Frolla, Franco Daniel (2021)
Soil organic carbon (SOC) is a key factor affecting soil physical fertility, as it improves several soil properties such as infiltration, structural stability, porosity, aeration and structure. It also improves soil chemical fertility since C is part of the soil organic matter, which constitutes the main reservoir of nutrients for crops (nitrogen, sulfur, zinc, among others). SOC is positively correlated with soil microbial biomass that acts on nutrient cycling and metabolization processes of toxic molecules. The total SOC stock in topsoil (0-30cm) is about 19.7 Pg C (FAO-ITPS GSOC map, 2018). Thus, due to the size of the soil carbon pool, even small increments in the net soil C storage may represent a substantial C sink potential. Although agricultural greenhouse gas emissions (GHGs) contribute to an important share of Argentina GHG emissions (135.53 MtCO2eq, 37% of total country GHG emissions; SAyDS, 2019), increasing ASOC stocks through judicious land use and sustainable soil management (SSM) practices may represent an important strategy to reduce and mitigate GHG emissions. In Argentina, the total productive area is about 157 million hectares (INDEC, 2021). Agricultural área (croplands) is about 40 (forty) million hectares, predominantly under no tillage system (91% agricultural area; AAPRESID, 2020). Soybean is the main product (45 million tons in 17 million hectares), followed by corn (44 million tons in 6.3 million hectares), wheat (17 million tons in 6.5 million hectares), barley (4.1 million tons in 0.1 million hectares) and sunflower (2.7 million tons in 1.3 million hectares).The rest of the area (over 124 Million hectares) is occupied with grasslands and shrublands dedicated to livestock production, and other agricultural uses. In the last decade’s agricultural land increased and SOC content decayed. This process of land use change was explained by increasing soybean monoculture and displacing livestock area, reducing SOC content (Lavado & Taboada, 2009). There has been an intense expansion of agriculture at the expense of grasslands, native forests and other natural resources in semiarid, sub-humid and subtropical regions of the country (Volante et al., 2012). Currently, soils of the Chaco-Pampean region exhibit SOC levels between 40-70% of the contents of virgin soils (Alvarez & Steinbach, 2009; Sainz Rozas et al., 2011; Milesi Delaye et al., 2013). Several farming practices may be used to restore or diminish the SOC loss, reduce soil erosion, sequester atmospheric carbon dioxide (CO2 ) and improve the soil quality (Poffenbarger et al., 2020). Among these practices, the inclusion of cover crops (CC) during winter has been postulated as one of the most promising activities (Ruis & Blanco-Canqui, 2017). The inclusion of CC showed average SOC sequestration rates of 0.45 tC/ha/yr (± 0.03), in Argentina (Alvarez et al., 2017; Beltran et al., 2018; Romaniuk et al., 2018). Increasing nutrient availability, crop growth and residue returns by increasing fertilizer use showed an increment of SOC around 0.18 tC/ha/yr (± 0.03) (Duval et al., 2020; Restovich et al., 2019). The inclusion of cycles with perennial pastures in crop rotations showed average SOC sequestration rates of 0.76 tC/ha/yr (± 0.03), exhibiting the greatest potential to increase SOC stocks (Costantini et al., 2016; Gil et al., 2016). Sustainable soil management (SSM) practices (FAO, 2020) such as the above mentioned practices have demonstrated potential to increase SOC stocks in different agricultural systems in Argentina, and thus sequester atmospheric CO2 as SOC to mitigate GHG emissions. However, SOC sequestration from these practices show highly variable sequestration rates, depending on edapho-climatic conditions, land use and management, among other factors. It is therefore relevant to identify which regions, soils, climates and systems have a greater potential to increase SOC stocks, in order to establish priorities for research and implementation of private and public policies. In this Soil organic carbon (SOC) is a key factor affecting soil physical fertility, as it improves several soil properties such as infiltration, structural stability, porosity, aeration and structure. It also improves soil chemical fertility since C is part of the soil organic matter, which constitutes the main reservoir of nutrients for crops (nitrogen, sulfur, zinc, among others). SOC is positively correlated with soil microbial biomass that acts on nutrient cycling and metabolization processes of toxic molecules. The total SOC stock in topsoil (0-30cm) is about 19.7 Pg C (FAO-ITPS GSOC map, 2018). Thus, due to the size of the soil carbon pool, even small increments in the net soil C storage may represent a substantial C sink potential. Although agricultural greenhouse gas emissions (GHGs) contribute to an important share of Argentina GHG emissions (135.53 MtCO2eq, 37% of total country GHG emissions; SAyDS, 2019), increasing ASOC stocks through judicious land use and sustainable soil management (SSM) practices may represent an important strategy to reduce and mitigate GHG emissions. In Argentina, the total productive area is about 157 million hectares (INDEC, 2021). Agricultural área (croplands) is about 40 (forty) million hectares, predominantly under no tillage system (91% agricultural area; AAPRESID, 2020). Soybean is the main product (45 million tons in 17 million hectares), followed by corn (44 million tons in 6.3 million hectares), wheat (17 million tons in 6.5 million hectares), barley (4.1 million tons in 0.1 million hectares) and sunflower (2.7 million tons in 1.3 million hectares).The rest of the area (over 124 Million hectares) is occupied with grasslands and shrublands dedicated to livestock production, and other agricultural uses. In the last decade’s agricultural land increased and SOC content decayed. This process of land use change was explained by increasing soybean monoculture and displacing livestock area, reducing SOC content (Lavado & Taboada, 2009). There has been an intense expansion of agriculture at the expense of grasslands, native forests and other natural resources in semiarid, sub-humid and subtropical regions of the country (Volante et al., 2012). Currently, soils of the Chaco-Pampean region exhibit SOC levels between 40-70% of the contents of virgin soils (Alvarez & Steinbach, 2009; Sainz Rozas et al., 2011; Milesi Delaye et al., 2013). Several farming practices may be used to restore or diminish the SOC loss, reduce soil erosion, sequester atmospheric carbon dioxide (CO2) and improve the soil quality (Poffenbarger et al., 2020). Among these practices, the inclusion of cover crops (CC) during winter has been postulated as one of the most promising activities (Ruis & Blanco-Canqui, 2017). The inclusion of CC showed average SOC sequestration rates of 0.45 tC/ha/yr (± 0.03), in Argentina (Alvarez et al., 2017; Beltran et al., 2018; Romaniuk et al., 2018). Increasing nutrient availability, crop growth and residue returns by increasing fertilizer use showed an increment of SOC around 0.18 tC/ha/yr (± 0.03) (Duval et al., 2020; Restovich et al., 2019). The inclusion of cycles with perennial pastures in crop rotations showed average SOC sequestration rates of 0.76 tC/ha/yr (± 0.03), exhibiting the greatest potential to increase SOC stocks (Costantini et al., 2016; Gil et al., 2016). Sustainable soil management (SSM) practices (FAO, 2020) such as the above mentioned practices have demonstrated potential to increase SOC stocks in different agricultural systems in Argentina, and thus sequester atmospheric CO2 as SOC to mitigate GHG emissions. However, SOC sequestration from these practices show highly variable sequestration rates, depending on edapho-climatic conditions, land use and management, among other factors. It is therefore relevant to identify which regions, soils, climates and systems have a greater potential to increase SOC stocks, in order to establish priorities for research and implementation of private and public policies.